PERENCANAAN STRUKTUR BAJA GEDUNG KOMERSIAL (SMPN 50 BEKASI ) DENGAN METODE LRFD - Fazry Alwy Sirodz (SINERGI : Jurnal Riset Ilmiah, 2026)
The steel structure design for the SMPN 50 Bekasi commercial building was carried out to produce a safe, strong, and efficient structural system in terms of material usage and construction costs. The steel structure was selected based on its advantages of high strength, good ductility, and ease of fabrication and field implementation. The planning method used in this study is Load and Resistance Factor Design (LRFD), which considers load factors and strength reduction factors to ensure the structural safety level meets regulatory requirements. The structural design refers to Indonesian national standards, namely SNI 1729:2020 for steel structure specifications, SNI 1727:2020 for building loading, and SNI 1726:2019 for earthquake resistance. The planning stages include collecting building data, determining dead loads, live loads, and earthquake loads, modeling the structure using structural analysis software, and analyzing internal forces in the form of axial forces, bending moments, and shear forces. These internal forces are then used as the basis for designing the main structural elements, namely beams, columns, and steel connections, using the LRFD method. The design results indicate that the selected steel profile is capable of withstanding the factored load combination and meets the requirements for flexural, shear, and compressive strength, as well as structural stability. Therefore, the steel structure design for the SMPN 50 Bekasi commercial building using the LRFD method can be used as a reference for safe, efficient planning that complies with applicable regulations